Sutureless technique using the left atrial appendage for left pulmonary vein occlusion after catheter ablation - Naohiro Wakabayashi; Aina Hirofuji; Natsuya Ishikawa; Hiroyuki Kamiya (Surgical Case Reports)
Abstract Background Pulmonary vein stenosis or occlusion is a rare but one of the most devastating complications after catheter ablation for cardiac arrhythmias, and surgical repair is an option in severe cases. The sutureless technique, which avoids direct suture of vessel walls, was initially described for congenital pulmonary vein stenosis and has been widely performed due to its good restenosis-free rate. Case presentation A 52-year-old male developed left pulmonary vein occlusion after catheter ablation for atrial fibrillation. The surgical repair with sutureless technique using the left atrial appendage was performed without any complications. Postoperative computed tomography demonstrated the revascularization of the pulmonary vein. Conclusions The sutureless technique using the left atrial appendage is significantly reasonable particularly in case of left pulmonary vein stenosis or occlusion after catheter ablation for atrial fibrillation since it reduces the risks of restenosis and thromboembolism.